A translational cellular model for the study of peritubular cells of the testis. Issue 2 (August 2020) - Schmid, Nina; Missel, Annika; Petkov, Stoyan; Stöckl, Jan B; Flenkenthaler, Florian; Arnold, Georg J; Fröhlich, Thomas; Behr, Rüdiger; Mayerhofer, Artur
Abstract : Testicular peritubular cells (TPCs) are smooth muscle-like cells, which form a compartment surrounding the seminiferous tubules. Previous studies employing isolated human testicular peritubular cells (HTPCs) indicated that their roles in the testis go beyond sperm transport and include paracrine and immunological contributions. Peritubular cells from a non-human primate (MKTPCs), the common marmoset monkey, Callithrix jacchus, share a high degree of homology with HTPCs. However, like their human counterparts these cells age in vitro and replicative senescence limits in-depth functional or mechanistic studies. Therefore, a stable cellular model was established. MKTPCs of a young adult animal were immortalized by piggyBac transposition of human telomerase ( hTERT ), that is, without the expression of viral oncogenes. Immortalized MKTPCs (iMKTPCs) grew without discernable changes for more than 50 passages. An initial characterization revealed typical genes expressed by peritubular cells (androgen receptor ( AR ), smooth-muscle actin ( ACTA2 ), calponin ( CNN1 )). A proteome analysis of the primary MKTPCs and the derived immortalized cell line confirmed that the cells almost completely retained their phenotype. To test whether they respond in a similar way as HTPCs, iMKTPCs were challenged with forskolin (FSK) and ATP. As HTPCs, they showed increased expression level of the StAR protein ( StAR ) after FSK stimulation, indicating steroidogenic capacity. ATP increased the expression of pro-inflammatory factors (e.g. IL1B ; CCL7 ), as it is the case in HTPCs. Finally, we confirmed that iMKTPCs can efficiently be transfected. Therefore, they represent a highly relevant translational model, which allows mechanistic studies for further exploration of the roles of testicular peritubular cells.